ARTIFICIAL INTELLIGENCE AND THE EDUCATION SECTOR IN THE 21ST CENTURY (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
The article is dedicated to the impact of artificial intelligence (AI) on the education sector in the 21st century. It explores key aspects of AI integration into education, including personalized learning, teacher support, and the automation of administrative tasks. The article discusses the benefits of AI, such as improving the efficiency of educational processes and the ability to analyze large amounts of data for informed decision-making. It also addresses potential challenges and ethical issues related to AI implementation, including concerns about data privacy, algorithmic bias, and the threat of job displacement.